2002
DOI: 10.1046/j.1463-1326.2002.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arachidonic acid plus zinc on glucose disposal in genetically diabetic (ob/ob) mice

Abstract: AA plus zinc in drinking water is effective in decreasing blood glucose levels in obese mice. These results indicate that use of these compounds should be considered as a dietary supplement to control hyperglycaemia in patients with type II diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Moreover, although the detailed mechanisms are not clear, these complexes improve insulin resistance and may stimulate glucose utilization in peripheral tissues since they normalize the blood glucose level without increase the serum insulin level. Many researchers have reported that Zn(II) ions and complexes increased insulin sensitivity and promoted the utilization of glucose in peripheral tissues [41,42]. Our results did not contradict these reports.…”
Section: In Vivo Evaluation Of Anti-diabetic Effect Of Zn(2-ampy) 2 Csupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, although the detailed mechanisms are not clear, these complexes improve insulin resistance and may stimulate glucose utilization in peripheral tissues since they normalize the blood glucose level without increase the serum insulin level. Many researchers have reported that Zn(II) ions and complexes increased insulin sensitivity and promoted the utilization of glucose in peripheral tissues [41,42]. Our results did not contradict these reports.…”
Section: In Vivo Evaluation Of Anti-diabetic Effect Of Zn(2-ampy) 2 Csupporting
confidence: 64%
“…Our results did not contradict these reports. In the mean time, there are many reports about mechanisms of blood glucose lowering effect of Zn(II) compounds such as inhibition of hepatic glucose release or activation of Akt in adipocytes or fibroblasts [42,43]. In fact, Zn(II) complexes which were investigated in this study do not only partially affect in the body but may play an important role to show blood glucose lowering effect in the various tissues.…”
Section: In Vivo Evaluation Of Anti-diabetic Effect Of Zn(2-ampy) 2 Cmentioning
confidence: 86%
“…This effect was seen in both genetically IDE-deficient diabetic G-K rats, and in insulin resistant aged overweight Sprague-Dawley (S-D) rats (Song et al, 2003). However, in obese diabetic ob/ob mice, blood glucose levels were significantly decreased in the absence of increased plasma insulin levels (Hwang et al, 2002). These reports and our previous studies collectively suggest that ZA ameliorates insulin resistance and diabetes in humans by stimulating IDE synthesis.…”
Section: Introductionmentioning
confidence: 52%
“…Actually, most people are interested in high-calorie food which has a high risk for the development of diabetes mellitus [12,13] . Previous researches reported that AA alone had no therapeutic effect in genetically diabetic animal models [14,15] . However, AA's preventive effect on insulin resistance induced by diets in vivo has not been reported.…”
Section: Discussionmentioning
confidence: 94%